Aid Scaling Up : Do Wage Bill Ceilings Stand in the Way? - Fedelino, Annalisa (IMF Working Papers; Working Paper ;, 2006)
This paper assesses whether the scaling up of aid and the resulting increase in government spending that is needed to meet the Millennium Development Goals (MDGs) would be hampered by wage bill ceilings that are often part of government programs supported by the IMF's Poverty Reduction and Growth Facility (PRGF). Based on country case studies for 2003-05, the paper suggests that, in the past, wage bill ceilings have not restricted the use of available donor funds. Yet the paper offers a number of suggestions for further enhancing the flexibility of wage bill conditionality in PRGF-supported programs to respond to higher aid flows that may result in the future.